2022
DOI: 10.1111/1471-0528.17085
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and outcomes of sentinel lymph node mapping in women undergoing minimally invasive surgery for endometrial cancer

Abstract: To examine the patterns and outcomes of sentinel lymph node (SLN) assessment in women with endometrial cancer. Design: Retrospective cohort study. Setting: United States inpatient and outpatient hospital services. Population: Women with endometrial cancer who underwent a laparoscopic or robotic-assisted hysterectomy. Methods: The Perspective Database from 2012 to 2018 was used. Performance of lymph node dissection was classified as SLN mapping, lymph node dissection or no nodal evaluation. Adjusted regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…Dear Dr. Papageorghiou, We appreciate the commentary by Iavazzo and colleagues 1 regarding our article 'Uptake and outcomes of sentinel lymph node mapping in women undergoing minimally invasive surgery for endometrial cancer', which highlights the utilisation, morbidity and costs associated with sentinel lymph node (SLN) mapping in women undergoing minimally invasive hysterectomy for endometrial cancer. 2 We agree with the authors that in both prior studies and our study, SLN mapping was associated with reduced morbidity compared with lymphadenectomy and the importance of this in the quality of life of patients. 3 Although our study did show that SLN mapping is associated with increased costs as compared with no nodal evaluation, prior data has suggested that the increased perioperative costs of SLN mapping are offset by decreased downstream costs, such as frozen section and lymphadenectomy.…”
Section: Authors' Replysupporting
confidence: 92%
“…Dear Dr. Papageorghiou, We appreciate the commentary by Iavazzo and colleagues 1 regarding our article 'Uptake and outcomes of sentinel lymph node mapping in women undergoing minimally invasive surgery for endometrial cancer', which highlights the utilisation, morbidity and costs associated with sentinel lymph node (SLN) mapping in women undergoing minimally invasive hysterectomy for endometrial cancer. 2 We agree with the authors that in both prior studies and our study, SLN mapping was associated with reduced morbidity compared with lymphadenectomy and the importance of this in the quality of life of patients. 3 Although our study did show that SLN mapping is associated with increased costs as compared with no nodal evaluation, prior data has suggested that the increased perioperative costs of SLN mapping are offset by decreased downstream costs, such as frozen section and lymphadenectomy.…”
Section: Authors' Replysupporting
confidence: 92%
“…We hypothesize that this trend mainly reflects the concurrent increase in use of sentinel lymph node biopsy with robotic-assisted surgery for patients at potential risk of early endometrial cancer. 4,5 Although this is partly supported by the observation that the strongest association for nodal evaluation was performance of robotic-assisted surgery, the dataset does not provide information on whether sentinel node biopsy was performed. Our finding of increased use of nodal evaluation for patients with endometrial hyperplasia without atypia raises the potential risk of overtreatment in this population at low risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Early Complications While the landscape of lymph node staging in endometrial cancer is shifting from systematic lymphadenectomy to SLN biopsy, 16 data comparing a complications' profile of the two methods are lacking. Dioun et al 17 retrospectively analyzed a large database (n=45 381), and SLN mapping was associated with a decreased risk of complications compared with lymphadenectomy (5.9% vs 7.3%; RR=0.85, 95% CI 0.77 to 0.95) after adjusting for confounders. Accorsi et al 6 recorded higher intra-operative (RR=14.25, 95% CI 1.85 to 19.63) and 30-day complication rates (RR=3.11, 95% CI 1.62 to 5.98) for women who underwent lymphadenectomy compared with SLN mapping.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%